Convalescent plasma therapy for COVID-19 prophylaxis in adults early post-hematopoietic stem cell transplantation: one-year outcomes from a randomized controlled trial - Cao, Yigeng; Li, Qiang; Guo, Wenwen; Xu, Mingyue; Fang, Kuo; Wang, Fengjiao; Zhang, Rongli; Li, Lin; Wei, Jialin; Liu, Zhenyun; Liang, Chen; Zhai, Weihua; et al. (Frontiers in Immunology, 2025)
To evaluate the efficacy of COVID-19 convalescent plasma (CCP) in preventing SARS-CoV-2 infection in hematopoietic stem cell transplantation (HSCT) recipients during the early post-transplant period, a single-center, randomized controlled trial was conducted between June 2023 and February 2024. Seventy-two participants were randomized 1:1 to receive CCP (200 mL on days +14, +28, +2 months, and +3 months post-transplant) or standard treatment. The primary outcome was COVID-19 infection within 28 days after the last infusion; secondary outcomes included severe infection, adverse events, and survival. The CCP and standard treatment group each included 36 patients. In the CCP group, 26 (72.2%, 26/36) patients completed four cycles of plasma infusion and 33 (33/36, 91.7%) patients received at least one infusion. The median time to infection was 95 days (IQR 81-106) in the CCP group and 74 days (IQR 48-110) in the standard group (p = 0.272). The 120-day cumulative COVID-19 incidence was 32.1% (95% CI, 14.5-46.1%) in the CCP group and 22.9% (95% CI, 7.6-35.6%) in the standard treatment group (p=0.459). Severe cases occurred in one patient per group, with no 30-day mortality. One-year overall survival (OS) was lower in the CCP group compared to the standard treatment group (73.1% [95% CI, 59.4-90.0%] vs. 91.7% [83.1-100%], p=0.044). At 90 days post-transplantation, the peripheral blood CD4/CD8 ratio in patients of the CCP group was significantly lower than that in the standard treatment group (p = 0.008). Adverse events were observed in only 3 patients and were mild. CCP recipients had higher antibody levels, but differences were not significant. These findings indicate that CCP did not prevent COVID-19 infection and may have limited efficacy in early post-transplant patients.Clinical Trialshttps://clinicaltrials.gov/, identifier NCT05904067.